Pengaruh Akuntabilitas, Potensi Daerah dan Aset Daerah terhadap Transparansi Pemerintah Daerah - Rosalia, Rosalia; Zulkarnain, Pingky Dezar (Institut Bisnis dan Informatika Kesatuan, 2020)
This study aims to find out several factors that affect the transparency of local governments after the enactment of Law Number 14 of 2008 concerning the Freedom of Information Act. This research focuses on the practice of the publication of local government financial statements and information about the local budget (APBD) on the website of each local government. The identified factors (independent variables) are accountability, regional potential and regional assets. In addition to knowing the partial effect of the independent variables on dependent variables, this study also aims to determine whether the accountability, regional potential, and regional assets simultaneously influence the transparency of regional government. The population of this study is 28 local governments in the province of West Java during the period of 2016 – 2018. Thus, the total number of samples is 84 . The type of data is secondary data. The analytical tool used is SPSS 24 for windows software. The analytical method is logistic regression analysis with a significance level of 5% The results show that accountability, regional potential and regional assets simultaneously influence the transparency of local government. The accountability variable that is proxied into audit opinion does not affect the transparency of local government. This means that the WTP opinion obtained by the regional government does not encourage the regional government to practice the publication of financial statements and APBD information on the respective regional government website. Furthermore, regional potential variables significantly influence the transparency of local governments. The higher regional potential, the greater the supervision of the community regarding the management of the region’s potential is. This encourages the regional government to be more transparent with its financial statements. The regional asset variable does not significantly influence regional transparency. This shows that high regional fixed assets does not directly make regional governments more transparent in disclosing their financial statement to the public. Key words : Accountability, Regional potential, Regional Asset, Publication, Transparency, Website